Realizacja postulatów wyborczych partii politycznych w Niemczech na rzecz ochrony klimatu - kwestia "odejścia od węgla" = Implementation of the election postulates of political parties in Germany to protect the climate - the issue of "coal exit" - Molo, Beata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article focuses on the problem of implementing the demands for climate protection contained in the election programs of political parties in Germany in the 2017 Bundestag elections, with particular emphasis on the issue of phasing out coal for energy production.
Keywords: Niemcy; postulaty wyborcze; ochrona klimatu; "odejście od węgla"; Germany; election postulates; climate protection; "coal exit"